Young Generations’ Perception of Deadwood in Forest Landscapes: Insights from Turkish Students - Selim Bayraktar; Claudia Becagli; Alessandro Paletto (South-East European Forestry)
Recently, citizens’ perceptions toward deadwood in forests have become increasingly important in recreational forests for socially sustainable management. The present study aims to investigate how deadwood in forests is perceived by the young generations (university and post-university students). This study was implemented by submitting a web-based questionnaire to 485 Turkish students. The results showed that our student sample perceived the key role in deadwood for soil fertilization, the provision of microhabitats, and food for wildlife. A high percentage of students positively viewed lying deadwood in forests, while standing dead trees were less positively perceived. The socio-demographic characteristics of respondents (gender and age) played a key role in explaining the variations in individual preferences toward deadwood. In conclusion, the results of this study highlight that despite students’ awareness of the ecological role of deadwood in forests, aesthetically they still prefer forests with moderate amount of deadwood or without deadwood. The findings obtained in this study can help decision-makers define a socially accepted forest management strategy.